El juego y las habilidades sociales en los niños de la Institución Educativa Inicial N° 847 Nuestra Señora de la Purísima, Punchana 2022 - Rengifo Montes de Bocanegra, Nitsy (2023)
The study was carried out with the objective of determining the correlation between play and social skills in children of the Initial Educational Institution No. 847 "Nuestra Señora de la Purisima" Punchana 2022 This research was of the relational quantitative type and the research design is non-experimental, correlational and transactional. The population consisted of 100 children, and census sampling was applied. In this study, observation was used to obtain the data and an observation guide was used to obtain the data; the tools were previously tested for validity and reliability by professionals with expertise in the variables. The final result: in the statistical test of correlation p=0.123 was obtained, concluding that there is no strong correlation between play and social skills of the children of the I.E.I N° 847 "Nuestra Señora de la Purisima" Punchana 2022